2000
DOI: 10.1051/agro:2000177
|View full text |Cite
|
Sign up to set email alerts
|

Cereal variety and species mixtures in practice, with emphasis on disease resistance

Abstract: Variety mixtures can provide functional diversity that limits pathogen and pest expansion, and that makes use of knowledge about interactions between hosts and their pests and pathogens to direct pathogen evolution. Indeed, one of the most powerful ways both to reduce the risk of resistance break-down and to still make use of defeated resistance genes is to use cereal variety and species mixtures. The most important mechanisms reducing disease in variety and species mixtures are barrier and frequency effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
245
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(276 citation statements)
references
References 62 publications
6
245
2
1
Order By: Relevance
“…This may at least partially explain the greater protection in the plots with greater proportions of the resistant genotype, which impeded larger amounts of inoculum from reaching the susceptible material. According to Finckh et al (2000), artificial inoculation may reduce the efficiency of mixtures regarding the control of disease in plants. Assessing sorghum plants with mixtures of the BR009B (susceptible to anthracnose), BR008 (partially resistant to anthracnose) and CMSXS210B (resistant to anthracnose), Guimarães et al (1998) found that the plots with these mixtures reduced disease severity by as much as 78% and concluded that a greater proportion of the resistant genotype units led to a greater reduction in disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…This may at least partially explain the greater protection in the plots with greater proportions of the resistant genotype, which impeded larger amounts of inoculum from reaching the susceptible material. According to Finckh et al (2000), artificial inoculation may reduce the efficiency of mixtures regarding the control of disease in plants. Assessing sorghum plants with mixtures of the BR009B (susceptible to anthracnose), BR008 (partially resistant to anthracnose) and CMSXS210B (resistant to anthracnose), Guimarães et al (1998) found that the plots with these mixtures reduced disease severity by as much as 78% and concluded that a greater proportion of the resistant genotype units led to a greater reduction in disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…It uses hybrid breeding methods and quantitative genetics and sets out to describe the general mixing ability (GMA, the mean value for all associations) and/or the specific mixing ability (SMA, the interaction between two given species or cultivars). This was first developed for cultivar mixtures (reviewed in Dawson and Goldringer 2012;Gizlice et al 1989;Knott and Mundt 1990;Lopez and Mundt 2000), but can be extended directly to multiple cropping systems (Gallais 1970;Finckh et al 2000;Finckh and Wolfe 2006), and temporal successions of crops, even though this has not yet been proposed. Ideotypes can be developed by quantitative trait loci (QTL) detection or genomic selection methodologies, using markers to tag the genomic areas with the greatest positive interactions between genotypes or species (complementation/ facilitation).…”
mentioning
confidence: 99%
“…It has been shown that the intensification of the disease caused by monoculture could be avoided by retaining diversity within the cereal crops (Finckh et al 2000;Newton et al 2009). Our study has shown that cultivation of varieties of spring barley in mixtures reduces the intensity of powdery mildew disease when compared to pure stands.…”
Section: Discussionmentioning
confidence: 60%
“…Genetic diversity in mixed stands is increased when compared to pure stands. Main advantages of cultivating crops in variety mixtures involve an increased genetic distance between plants with the same genetic resistance to diseases, restriction of pathogen spread by resistant plants which form a natural barrier, competitive interactions among host plants affecting their disease susceptibility (Finckh et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation